ANALYSIS OF FINANCIAL FEASIBILITY AND BUSINESS DEVELOPMENT STRATEGY OF OYSTE MUSHROOM BAG LOG AS A EFFORT TO OVERCOMEFARM LABOUR POVERTY AT JEMBER REGENCY - Hawa, Tidar Aden; Zuniana, Qory (Universitas Muhammadiyah Jember, 2020)
Jember regency is faced with the problem of high poverty rate. Poor population were dominated by farm laborers. The free time they have every day is an opportunity to find additional job. Paguyuban